The Role of Financial Attitude in Mediating The Relationship Between Financial Knowledge and Financial Management Behavior in Batam City - Yeolencia, Erinne; Lestari, Emi (JEM17: Jurnal Ekonomi Manajemen, 2024)
This study aimed to analyze the effect of financial Knowledge and financial attitudes on financial management behavior in Batam City. This study used a non-probability sampling method. The sampling technique used was purposive sampling. The sample of this research is people from Batam City with 260 respondents. The data collection method was carried out by distributing online and offline questionnaires, which were then analyzed using the SmartPLS version 4.0 program, which included descriptive and inferential statistical analysis. The results showed that financial Knowledge and financial attitude had a positive and significant effect on financial management behaviour, financial knowledge had a positive and significant effect on financial attitude, and financial attitude mediates a positive and significant relationship between financial Knowledge and financial management behaviour in Batam City. Keywords:Financial Knowledge, Financial Attitude, Financial management Behavior